Synthesis and enhanced magnetoelectric properties of (1−x)Pb(Zr0.52Ti0.48)O3+(x)Co0.9Mn0.1Fe2O4 composites. Issue 4 (March 2019) - Atif, M.; Atta-ur-Rehman; Ahmed, S.; Nadeem, M.; Khalid, W.; Ali, Z.; Yaqoob Khan, M.
Abstract: Magnetoelectric (ME) ( 1 − x ) Pb ( Zr 0.52 Ti 0.48 ) O 3 + ( x ) Co 0.9 Mn 0.1 Fe 2 O 4 composites were prepared by mixed oxide route. XRD analysis revealed development of two-phase composites with distinct ferroelectric ( Pb ( Zr 0.52 Ti 0.48 ) O 3 ) and ferrite ( Co 0.9 Mn 0.1 Fe 2 O 4 ) phases. However, Rietveld refinement confirmed the coexistence of tetragonal and rhombohedral perovskite structures for Pb ( Zr 0.52 Ti 0.48 ) O 3 phase while cubic spinel structure for Co 0.9 Mn 0.1 Fe 2 O 4 phase. Impedance spectroscopy was employed to investigate the effect of constituent phases on the conduction mechanism, dielectric relaxation and resistive properties of prepared composites. It was found that small amount of Mn substituted in Co Fe 2 O 4 not only improved the resistive properties of ferrite phase but also enhanced the ME coupling coefficient ' α E ' in the prepared composites. The obtained value of α E was found to be two orders of magnitude higher in comparison to the Pb ( Zr 0.52 Ti 0.48 ) O 3 − Co Fe 2 O 4 composites with similar wt% compositions. The observed enhancement in α E is explained in terms of dense microstructure, better phase connectivity and increased resistivity of ferrite phase.